2015
DOI: 10.1128/aem.01098-15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome of Truffles in Aroma Formation: a Meta-Analysis Approach

Abstract: dTruffles (Tuber spp.) are ascomycete subterraneous fungi that form ectomycorrhizas in a symbiotic relationship with plant roots. Their fruiting bodies are appreciated for their distinctive aroma, which might be partially derived from microbes. Indeed, truffle fruiting bodies are colonized by a diverse microbial community made up of bacteria, yeasts, guest filamentous fungi, and viruses. The aim of this minireview is two-fold. First, the current knowledge on the microbial community composition of truffles has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 43 publications
4
123
0
2
Order By: Relevance
“…Among cultivated Ascomycetes, truffles are colonized by microbes at all stages of their life cycle: symbiotic stage (ectomycorrhiza), fruiting bodies and mycelia (Vahdatzadeh et al, 2015). Black truffle ascocarps provide an habitat to complex bacterial communities, which is dynamic and evolves during the maturation of the ascocarps (Antony-Babu et al, 2014).…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Among cultivated Ascomycetes, truffles are colonized by microbes at all stages of their life cycle: symbiotic stage (ectomycorrhiza), fruiting bodies and mycelia (Vahdatzadeh et al, 2015). Black truffle ascocarps provide an habitat to complex bacterial communities, which is dynamic and evolves during the maturation of the ascocarps (Antony-Babu et al, 2014).…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 99%
“…Black truffle ascocarps provide an habitat to complex bacterial communities, which is dynamic and evolves during the maturation of the ascocarps (Antony-Babu et al, 2014). Interestingly, bacteria, the dominant kingdom among truffle-associated microorganisms, have been postulated to be the most important contributors to truffle aromas (Vahdatzadeh et al, 2015). This raises the intriguing possibility that in a natural setting, the VOCs released by the bacterial microbiome of truffles play an important role in attracting the mammals and insects that act as vectors for truffle dispersal.…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 99%
“…Alphaproteobacteria and Deltaproteobacteria (both in the phylum Proteobacteria) were found to be more abundant in the rhizosphere soil of root tip‐cut or 10 mg l −1 uniconazole‐treated colonized seedlings than in control rhizosphere soil. Previous studies also found that α‐Proteobacteria and γ‐Proteobacteria comprised the predominant components of the bacterial communities of truffles (Barbieri et al , ; Vahdatzadeh et al , ; Li et al , ). Previous studies have demonstrated that Pseudomonas fluorescens (Proteobacteria) improved the establishment and functioning of ectomycorrhizal symbiosis (Dominguez et al , ).…”
Section: Discussionmentioning
confidence: 80%
“…They can promote the growth of plants, increase the uptake of mineral elements and enhance the tolerance of plants to stress including drought stress, high salinity stress and disease stress (Abiala et al , ; Bell et al , ; Alegria Terrazas et al , ; Baldrian, ). Bacteria in the soil or associated with truffle ascocarps were found to play important roles in truffle maturation and production of volatile organic compounds (Barbieri et al , ; Antony‐Babu et al , ; Splivallo et al , ; Vahdatzadeh et al , ). Mycorrhiza helper bacteria (MHB) are a group of organisms that could stimulate the formation of mycorrhizal symbiosis (Deveau and Labbé, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the odor characteristics of T. magnatum and T. japonicum had obvious differences. Many reports have shown that truffle aroma varies depending on the ripening stage (Saltarelli et al, 2008;Zeppa et al, 2004), with some assessing the microorganisms involved in forming the truffle aroma (Splivallo et al, 2015;Vahdatzadeh, Deveau, & Splivallo, 2015). Many reports have shown that truffle aroma varies depending on the ripening stage (Saltarelli et al, 2008;Zeppa et al, 2004), with some assessing the microorganisms involved in forming the truffle aroma (Splivallo et al, 2015;Vahdatzadeh, Deveau, & Splivallo, 2015).…”
Section: Volatile Compoundsmentioning
confidence: 99%